POTENSI BIOMASSA KARBON TEGAKAN, NEKROMAS (NECROMASS) DAN SERESAH (LITTER) PADA HUTAN PENELITIAN DRAMAGA - Hendrawan, Fulki; Satjapradja, Ombo; Dharmawan, I. Wayan S (Jurnal Nusa Sylva, 2014)
Human activity and environmental damage increased has led to high level of carbon emission in the atmosphere and led to the global warming. Reducing of carbon emission through sink program which requires estimation data of biomass carbon stock. The aim of this study to determine the potential of stand biomass carbon stock, necromass and litter. The study conducted from April-May 2013. Research location was executed in Dramaga Research Forest, Bogor. The results of this study indicate that potential of biomass carbon stock in Dramaga Research Forest were 225.51 ton biomass/ha and 105.99 ton carbon/ha (trees); 16.00 ton biomass/ha and 8.10 ton carbon/ha (poles); 19.11 ton biomass/ha and 8.98 ton carbon/ha (saplings); 2.01 ton biomass/ha and 0.94 ton carbon/ha (seedlings); 0.92 ton biomass/ha and 0.43 ton biomass/ha (undergrowth); 0.41 ton biomass/ha and 0.19 ton carbon/ha (necromass); 0.86 ton biomass/ha and 0.41 ton carbon/ha (litter). The species dominant for carbon stock are Pinus merkusii, Shorea guiso, Tectona grandis, Dipterocarpus trinervis, Shorea balangeran, Pterygota alata, Hopea mengarawan, Protium javanicum, Quercus sp. and Shorea leprosula.